The benefits of diversification in ASEAN stock market to Malaysia investors - Goh, Q. R.; Md Nasir, Annuar; Mohd Ashhari, Zariyawati (Canadian Center of Science and Education, 2014)
The establishment of ASEAN Exchange had removed the barriers and hassles from investors in six ASEAN member countries to invest freely and easily within the six countries' stock market, including Malaysia. This study aimed to analyse whether the establishment of ASEAN Exchange, can provide diversification benefit to Malaysian investors compared with their domestically diversified portfolio. The analysis is done based on 25 companies which selected from each participating ASEAN country by using Efficient Frontier Model. In addition, Sharpe Ratio had also been developed and analysed to provide an insight to Malaysia and ASEAN investors regarding the attractiveness of each ASEAN market. The results of this study conclusively show that an ASEAN level of diversification does bring benefits to Malaysian investors, as ASEAN portfolio outperforms all individual country's portfolio.